Kritik Epistemologis Jacques Rancière atas Marxisme Struktural Louis Althusser - Tedy Aprilianto (Media: Jurnal Filsafat dan Teologi, 2026)
This paper critically examines Jacques Rancière rejection of Althusser’s concept of interpretation in epistemological rupture. Rancière critique stems from his rejection of hierarchical epistemological structures in the dichotomy between science and ideology. For Rancière, this approach actually constrains the division of social aesthetics of class outside of power as an ideological object, rather than  as an autonomous political subject. By examining the original works of Rancière and Althusser, the author uses a qualitative research model. Through this research model, the author analyzes Rancière's critique of Althusser in terms of elitism, epistemological break, and the separation of science and politics using hermeneutics. The results of this research contain hermeneutic arguments that emphasize that the interpretation of Marxismmust be grounded withinsocial aesthetics. This can happen because Ranciere attempts to present the progressive side of the Marxist tradition that has collapsed due to Althusser's concept of epistemological break.